Anaesthesia Protocol for Castration in a Dog with Dilated Cardiomyopathy – A Case Report - R.S. Ghag; Arun Prakash; V. Rahul; R. Pillai; Joby George (The Indian Veterinary Journal, 2023)
A five and half year’s old, intact male Golden retriever dog was presented with the history of cough, lethargy and weight loss, since a week. Dilated cardiomyopathy was confirmed using thoracic radiography and echocardiography. The dog was treated with pimobendan, benazepril and spironolactone orally for a month and the symptoms subsided.One month later the pet was presented for constipation and difficulty in passing stools. Abdominal ultrasound confirmed enlarged prostate gland and castration was decided. The animal was anaesthetized using butorphanol as pre-anaesthetic, ketamine and diazepam as induction and maintained with isoflurane. The animal had an uneventful recovery and details will be discussed.